Psychological interventions for trauma in individuals who have psychosis: A systematic review and meta-analysis. Issue 1 (2nd January 2017) - Sin, Jacqueline; Spain, Debbie
Abstract : Background: Psychological interventions, in particular those derived from cognitive-behavioural therapy frameworks, and eye movement desensitisation and reprocessing, are effective for reducing post-traumatic stress disorder and associated distress. To date, studies have tended to exclude individuals who have psychosis; a clinical population who are known to be at risk of experiencing trauma. Whether people with psychosis also benefit from trauma-focussed psychological therapies (TFPT) warrants further investigation. Method: A systematic search for randomised controlled trials was undertaken. Data were synthesised using narrative and meta-analytic approaches. Results: Five studies met the review inclusion criteria. Study findings overall indicate that TFPT are effective for reducing intrusive thoughts and images, negative beliefs associated with traumatic memories, hypervigilance, and avoidance. Limited data were available about the utility of interventions for improving mood, anxiety and quality of life. Attrition rates were comparable for participants offered active and control conditions. Conclusion: Findings are consistent with those reported for the non-psychosis population. Future studies should establish which interventions are more acceptable and glean more favourable outcomes for this clinical population.